2018
DOI: 10.1016/j.ibmb.2018.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-specific transcription of proteases and nucleases across the accessory salivary gland, principal salivary gland and gut of Nezara viridula

Abstract: The phytophagous stink bug, Nezara viridula (L.) infests multiple plant species and impacts agricultural production worldwide. We analyzed the transcriptomes of N. viridula accessory salivary gland (ASG), principal salivary gland (PSG) and gut, with a focus on putative digestive proteases and nucleases that present a primary obstacle for the stability of protein-or nucleic acid-based stink bug control approaches. We performed high throughput Illumina sequencing followed by de novo transcriptome assemblies. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 41 publications
3
31
0
Order By: Relevance
“…In addition, certain numbers of the transcripts identi ed from the proteomic pro les were associated with the increase of the FPKM (expected number of Fragments Per Kilobase of transcript sequence per Million base pairs sequenced) value of the transcripts (Fig. 2b), which were similar to the previous observations in the investigation of proteases of stinkbugs [21,26].…”
Section: ) Mapping Of the Assembled Genes To The Proteomic Pro Les Dsupporting
confidence: 88%
See 1 more Smart Citation
“…In addition, certain numbers of the transcripts identi ed from the proteomic pro les were associated with the increase of the FPKM (expected number of Fragments Per Kilobase of transcript sequence per Million base pairs sequenced) value of the transcripts (Fig. 2b), which were similar to the previous observations in the investigation of proteases of stinkbugs [21,26].…”
Section: ) Mapping Of the Assembled Genes To The Proteomic Pro Les Dsupporting
confidence: 88%
“…Transcriptomic analysis coupled with proteomic pro ling is an effective strategy for identi cation of functional proteins in the SG and gut of hemipterans [21,26]. For example, proteases in the SG and gut of the two devastating pentatomid stink bugs, Halyomorpha halys and Nezara viridula, were investigated to identify proteases highly expressed in each tissue [21,26]. Furthermore, mapping of SG transcripts of H. halys to the protein pro les of watery saliva, which is the saliva secreted into the host plants, revealed 22 abundant digestive proteases.…”
Section: Introductionmentioning
confidence: 99%
“…It has been also reported that the transcriptome of the stink bug Nezara viridula contains around 134 nucleases secreted by the gut and salivary gland. These studies provided an insight into the abundance of nucleases in insects, their broad substrate specificity, and their highly evolved physiology …”
Section: Dsrna Inside the Gutmentioning
confidence: 99%
“…These studies provided an insight into the abundance of nucleases in insects, their broad substrate specificity, and their highly evolved physiology. 25 There are also a large number of insects with extra-oral digestion. They inject into or salivate externally on food to get it to break down before consumption.…”
Section: Digestive Nucleasesmentioning
confidence: 99%
“…Most proteolytic activity occurs in M2 and M3 (Cantón and Bonning, 2019) mediated by the cysteine proteases Cathepsin B and L, while M4 functions to house endosymbiotic bacteria (Hosokawa et al, 2016). The proteases and nucleases present in saliva, salivary glands, and midgut tissues of N. viridula have been cataloged (Liu et al, 2018). The manner in which these myriad digestive enzymes are employed for digestion of plant material of varied composition is unclear.…”
Section: Introductionmentioning
confidence: 99%